Global biographies : lived history as method - Almagor, Laura; Ikonomou, Haakon A.; Simonsen, Gunvor (Manchester University Press, 2022)
Global biographies offers a thorough historiographical intervention, a new set of biographical approaches to global history - 'time and periodization', 'exceptional normal' and 'space and scales' - and a broad and critically reflective set of case-studies spanning the globe.